POTRET KEMISKINAN DALAM KUMPULAN CERITA PENDEK TAWA GADIS PADANG SAMPAH KARYA AHMAD TOHARI - Hubbi Saufan Hilmi; Achmad Sultoni (Balai Bahasa Sumatera Utara, 2019)
This study aims to describe the portrait of poverty that exist in a collection of short stories the Tawa Gadis Padang Sampah by Ahmad Tohari. The method of this research is qualitative desktiptif method with the study of the sociology of literature. The source of the data in this study is a collection of short stories the Tawa Gadis Padang Sampah by Ahmad Tohari, book the theory of sociology of literature and related journals. The data in this research in the form of sentences that indicate problems in research. Data collection techniques in the study is the analysis of the techniques document. Data analysis techniques using interactive analysis techniques (interactive model of analysis). The results showed that the portrait of poverty in a collection of short stories the Tawa Gadis Padang Sampah by Ahmad Tohari is shown by the residence or the place of residence, employment or profession of a character who was involved the tevye, consumption or food, until the purchasing power of the character, as well as the role of a character in the short story.